Community management of rural aqueducts in the comunera province : an approach to its study from the perspective of legal pluralism - Guauque Torre, César (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This paper constitutes a first progress report of the research project “Community management of aqueducts, regulatory aspects: characterization of experiences in the commune province (Santander Department), Colombia 2019-2020. The problem to be developed raises the dislocation between the spaces state public and community public about the regulation of rural aqueducts trying to establish the way in which such regulation has been developed in its operation and management. The methodological approach is qualitative, with a phenomenological-hermeneutical focusing, as it seeks to approach the lived experience of the communities around the object of study, clarifying the meaning frameworks on the law produced in that social space. To that extent, the analysis is framed within the theories of legal pluralism from where some categories and variables are proposed for the characterization of the phenomenon. The work links the background check with the results of the first phase of contact and dialogue with the relevante social actors on the subject which took place in the fórum “Community management of aqueducts in the commune province”. In a later report, the results of the immersion and practice phase of the instruments for collecting empirical information will be presented.